2009
DOI: 10.1109/jsen.2009.2027411
|View full text |Cite
|
Sign up to set email alerts
|

Lamb Wave Sensor for Viscous Fluids Characterization

Abstract: This paper is a study of a new sensor for fluid characterization. This sensor is composed of a stainless steel plate in contact with a viscous material. The aim is to characterize the material viscosity by using reflected Lamb waves at the boundary interface. In order to identify the effects on the Lamb reflected modes by the viscous material, a complete study of the propagation wave in the alone plate is first presented. The propagation modes of the loaded plate are then investigated. By monitoring the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The reason for this dominance depends on a property of the material called acoustic impedance. The acoustic impedance of a solid material is the product of the density and velocity of dilatational wave, while the acoustic impedance of viscous fluid is given by the square root of the product of density and viscosity (Chancellier et al., 2009).
Figure 1.Variation of reflection coefficient (z1 s) with angle of incidence.
Figure 2.Variation of reflection coefficient (z2 s) with angle of incidence.
Figure 3.Variation of reflection coefficient (z3 s) with angle of incidence.
Figure 4.Variation of reflection coefficient (z4 s) with angle of incidence.
Figure 5.Variation of transmission coefficient (z1 f) with angle of incidence.
…”
Section: Numerical Computations and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this dominance depends on a property of the material called acoustic impedance. The acoustic impedance of a solid material is the product of the density and velocity of dilatational wave, while the acoustic impedance of viscous fluid is given by the square root of the product of density and viscosity (Chancellier et al., 2009).
Figure 1.Variation of reflection coefficient (z1 s) with angle of incidence.
Figure 2.Variation of reflection coefficient (z2 s) with angle of incidence.
Figure 3.Variation of reflection coefficient (z3 s) with angle of incidence.
Figure 4.Variation of reflection coefficient (z4 s) with angle of incidence.
Figure 5.Variation of transmission coefficient (z1 f) with angle of incidence.
…”
Section: Numerical Computations and Discussionmentioning
confidence: 99%
“…The reason for this dominance depends on a property of the material called acoustic impedance. The acoustic impedance of a solid material is the product of the density and velocity of dilatational wave, while the acoustic impedance of viscous fluid is given by the square root of the product of density and viscosity (Chancellier et al, 2009).…”
Section: Numerical Computations and Discussionmentioning
confidence: 99%
“…It has been shown that Lamb waves are advantageous for stationary mechanical waves generated in liquid media and especially for sensing applications [28,29]. Antisymmetric Lamb waves exhibit a relatively high quality factor in liquid compared to other out-of-plane flexural modes of vibration due to a lower damping in liquid at low frequency [30].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [3] developed out a new method that involves the application of embedded piezoelectric sensors so that monitoring can be determined by analyzing the velocity curves. Wilkie-Chancelie et al [4] designed an innovative sensor that is contacted to the viscous material and employs a reflected Lamb wave at the interface as the index to indicate the viscosity change of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoelectric-based sensors are considered adaptive for viscosity monitoring due to its quick-response, high-accuracy, and low-maintenance needs. Wilkie-Chancellier et al [4] used a piezoelectric plate as the sensor and applied guided wave (Lamb wave) to monitor the mechanical impedance and then obtain the viscosity of the tested material. This method was found to be valid only when the tested material is a weak fluid, that is, it should have Newtonian properties.…”
Section: Introductionmentioning
confidence: 99%